TINGKAT KEPUASAN PESERTA LELANG TERHADAP PELAYANAN TEMPAT PELELANGAN IKAN (TPI) MORODEMAK - dian ayunita nugraheni nurmala dewi (Akuatik: Jurnal Sumberdaya Perairan, 2019)
Objectives of this study were analyze fish auction participant satisfaction to auction services in TPI Morodemak, analyze attributes effect, services that fit to service quality measurement, and analyzed fish auction participants perception to performance and importance for fish auction house Morodemak services. Used descriptive method and purposive sampling with 49 respondents consists of commercial fishmongers, traditional fishmongers, purse seine owners, and boat lift net owners as fish auction participant. Satisfication measurement used Customer Satisfication Index (CSI), Importance and Performance Analysis (IPA) and gap analysis. Results from this study were value CSI 20% (0.2) indicate the auction participants dissatisfied with the services provided, IPA show there are four attributes should be develop, two elements have not been completed based on measurement requirements of service satisfaction, gap value average -0.05 means the auction participants were not satisfied with the performance of TPI services because the performance value was lower than the importance value.